Lastnosti in možnosti uporabe dendritičnih celic, antigensko specifičnih modulatorjev imunskega odziva - Repnik, Urška (Zdravniški vestnik, 2004)
Background. Since the discovery of dendritic cells (DC) more than 30 years ago, several types of DC have been isolated in mouse and human and methods fortheir in vitro generation have been developed, Their general characteristics are, the extensive expression of MHC class 11 molecules on their cell surfaces, the ability to take up, process and present antigens, selective migration through tissues and interaction with lymphocytes. Once they were reknown for their stimulatory role in T cell proliferation and CTL generation but tolerogenic types have since been described which cantribute tothe maintenance of tolerance to self antigens. Cructial for the defence against pathogens are Langerhans cells and dermal or interstitial DC that reside in the peripheral tissues and take up antigens. Then they migrate to lymph nodes or spleen and present the antigens to T cells. If infectious or inflammatory signals/factors are present in the periphery, DC begin to expresscostimulatory molecules and secrete cytokanes which enable them to trigger immune response, and in addition, influence its characteristics and shape the effector mechanisms. Conclusions. There is a great hope that in the near future ex vivo differentiated DC, equipped with selected antigens could be used for the treatment of cancer, autoimmune diseases and for the prevention of rejections following tissue and organ transplantations.
Keywords: Antigen Presentation; Antigen, predstavitev; Antigeni, CD; Antigens, Cd; Celične kulture; Cells, Cultured; Dendritic Cells; Dendritične celice; Limfocit, transformacija; Limfociti T; Lymphocyte Transformation; T-Lymphocytes